Strandings of northern bottlenose whales, Hyperoodon ampullatus, in the north-east Atlantic: seasonality and diet. (September 2014) - Fernández, Ruth; Pierce, Graham J.; MacLeod, Colin D.; Brownlow, Andrew; Reid, Robert J.; Rogan, Emer; Addink, Marian; Deaville, Robert; Jepson, Paul D.; Santos, M. Begoña
<x content-type="archive" xml:space="preserve">Abstract</x> Peaks in northern bottlenose whale, Hyperoodon ampullatus, strandings are found between August and September in the UK and August and November in The Netherlands, consistent with a hypothesized southward migration. However, results on diet suggest that several whales stranded during these months were not travelling from northern latitudes prior to stranding. We analysed the stomach contents of ten whales stranded in the north-east Atlantic (Scotland, N = 6, England, N = 1, Ireland, N = 2 and The Netherlands, N = 1). All but one of the analysed whales (live-stranded in the River Thames in January 2006) stranded between August and October. Food remains consisted almost entirely of cephalopod mandibles. Twenty-one cephalopod species (16 families) were recorded, the most abundant taxa being Gonatus spp., Teuthowenia spp. and Taonius pavo. No fish and few crustacean remains were found. Small amounts of cephalopod flesh were found in three of the stomachs and none in the others. Given that cephalopod beaks can remain within the stomach for several days, and that there was no evidence of inshore feeding (no coastal species were present among the prey), the whales may not have fed for several days prior to stranding. Three whales had remains of warm-temperate water cephalopods (e.g. Vampyroteuthis infernalis, Heteroteuthis sp.) in their stomachs, while three individuals showed a high diversity of prey in their stomachs, suggesting that several of the whales could have been either travelling north or consistently feeding in temperate latitudes prior to stranding. As previously recorded in other deep diving teuthophagous cetaceans, two animals had ingested small amounts of plastic debris.